CeO2 nanocrystal-modified layered MoS2/g-C3N4 as 0D/2D ternary composite for visible-light photocatalytic hydrogen evolution: Interfacial consecutive multi-step electron transfer and enhanced H2O reactant adsorption - Zhu, Chengzhang; Wang, Yuting; Jiang, Zhifeng; Xu, Fanchao; Xian, Qiming; Sun, Cheng; Tong, Qing; Zou, Weixin; Duan, Xiaoguang; Wang, Shaobin (Applied catalysis. B, Environmental, 2019)
[Display omitted] •0D CeO2 nanocrystals were tightly anchored on the 2D layered MoS2/g-C3N4 nanosheets.•Strong electronic interactions and Ce3+ species resulted in the enhanced adsorption of reactant H2O molecule.•CeO2@MoS2/g-C3N4 exhibited an efficient H2 evolution activity even without a noble-metal cocatalyst.•The improved activity was attributed to decreased H2O adsorption energy and multi-step electron transfer. Developing low-cost and high-performance catalysts is significant to solar-to-fuel conversion. Here, the synthesis of zero-dimensional (0D) CeO2 nanocrystal-decorated two-dimensional (2D) layered hybrids of MoS2/g-C3N4 was reported for the first time. In the absence of noble-metal cocatalyst, the optimized ternary CeO2@MoS2/g-C3N4 still manifested high photocatalytic activity toward H2 generation, with a rate of 65.4 μmol/h, which is approximately 8.3 and 17.5-fold greater than g-C3N4 and CeO2, respectively. The corresponding apparent external quantum efficiency reached 10.35% at a wavelength of 420 nm. The superior photocatalytic behavior of CeO2@MoS2/g-C3N4 heterojunction could be ascribed to the positive synergetic effects of well-matched energy-level positions and effective charge separation arose from the multi-step electron transfer processes between Ce4+/Ce3+ reversibility pairs and heterostructures. Furthermore, the adsorption ability of reactant H2O molecules on CeO2@MoS2/g-C3N4 was investigated. Due to the interfacial electronic interaction and Ce3+ species, CeO2@MoS2/g-C3N4 presented more reaction active sites with enhanced adsorption capacity and decreased energy barrier for reactant H2O molecules adsorption, which collaboratively promoted photocatalytic water splitting. This study provides new insights into the rational design of inexpensive ternary photocatalyst with multilevel electron transfer for efficiently converting solar energy into hydrogen without noble metals.